Teori Kesetaraan Sumber Daya Dworkin Dalam Kerangka Keadilan Distributif Dan Implikasinya Terhadap Konstitusi Negara Kesejahteraan - Bello, Petrus CKL (Jurnal Hukum & Pembangunan, 2022)
According to Dworkin, the equality that must be pursued by a government is equality of resources, not equality of welfare, as emphasized by utilitarianism in its various versions. According to him, the concept of resource equality is superior in interpreting abstract ideas about human equality. First, the concept of resource equity avoids ambiguity in understanding distributive justice and, second, avoids divisions that contradict our intuition about justice, two problems that plague the formulation of welfare equality. Equality of resources is proposed by Dworkin in the framework of distributive justice. According to Dworkin, it is in this equality of resources between the principles of equality and personal responsibility that often conflict can be reconciled, of course, by finding other concepts that satisfactorily fulfill both, for example the concept of insurance. Distributive justice presupposes that there is a theory of freedom, although in this theory of resource equity the dangers of freedom and equality will conflict but the theory of freedom will eliminate that danger. The problem is that the political economy policies of a country are not only dictated by the Constitution but also by the free market system, in which the people buy and sell their products and work. Of course the results are not the same for all. Then how does the Constitution of the Indonesian Welfare State guarantee equality? Because the people cannot be responsible (cannot fully vote) and determine their place in the economy, nor are they responsible for their talents, good and bad luck in life. Meanwhile, if the government takes the extreme position of wanting to distribute welfare equally regardless of the people's choice for their work, then the government here is tantamount to failing to respect the responsibility of the people to make something in their lives.